2009
DOI: 10.1016/j.molbiopara.2009.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum merozoite surface protein 2 is unstructured and forms amyloid-like fibrils

Abstract: Several merozoite surface proteins are being assessed as potential components of a vaccine against Plasmodium falciparum, the cause of the most serious form of human malaria. One of these proteins, merozoite surface protein 2 (MSP2), is unusually hydrophilic and contains tandem sequence repeats, characteristics of intrinsically unstructured proteins. A range of physicochemical studies have confirmed that recombinant forms of MSP2 are largely unstructured. Both dimorphic types of MSP2 (3D7 and FC27) are equival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
99
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(115 citation statements)
references
References 79 publications
16
99
0
Order By: Relevance
“…Importantly, both the 3D7 and FC27 allelic forms of MSP2 showed the same phenotype of being carried into RBCs followed by rapid degradation. The 3D7 and FC27 alleles of MSP2 share N-and C-terminal regions but vary significantly in the central strain-specific region of the protein (46,(76)(77)(78). The observation that both MSP2 variants show the same localization and very precise timing of degradation postinvasion suggests that the functions of the 3D7 and FC27 forms of MSP2 are the same, despite any structural differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, both the 3D7 and FC27 allelic forms of MSP2 showed the same phenotype of being carried into RBCs followed by rapid degradation. The 3D7 and FC27 alleles of MSP2 share N-and C-terminal regions but vary significantly in the central strain-specific region of the protein (46,(76)(77)(78). The observation that both MSP2 variants show the same localization and very precise timing of degradation postinvasion suggests that the functions of the 3D7 and FC27 forms of MSP2 are the same, despite any structural differences.…”
Section: Discussionmentioning
confidence: 99%
“…MSP2 is the second most abundant merozoite surface protein in terms of copy number (42), and while a function for MSP2 has not been identified, this protein is refractory to genetic deletion and is thought to be essential (43). MSP2 is highly polymorphic; however, all alleles can be grouped as either 3D7-like or FC27-like based on tandem sequence repeats and flanking nonrepetitive dimorphic sequences, with both alleles sharing N-and C-terminal regions (44)(45)(46). Currently, the fate of MSP2 during invasion is unclear, and there is no evidence of MSP2 in culture supernatants (20,47).…”
mentioning
confidence: 99%
“…However, it was also observed that regions of MSP2 outside the conserved N-terminal domain were also important for fibril formation by MSP2. Interestingly, failure of mAb 6D8 in situ that reacted with the N-terminal conserved region of MSP2 was taken as indirect evidence of the presence of MSP2 on the merozoite surface as a homooligomer; no direct evidence for MSP2 fibril has been reported (53). A major difference between these two highly abundant blood stage proteins with regard to their intrinsic propensity to form fibrils is that although MSP2 is anchored to the merozoite surface via the GPI anchor, MSP3 is supposed to be present on the merozoite surface through association with other surface proteins (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Oligomerization of MSP3, as a soluble protein, is facile and likely inherent to its structure that includes the presence of leucine zipper-like sequences at the C terminus (40). In both the proteins, although small peptides based on the domains involved in fibril formation also form fibrils like the full-length proteins themselves, the sequences outside the fibril forming domains are also involved and/or assist in fibril formation by the two proteins (52,53). Results described in this study, however, clearly show that MSP3-based fibrils are present on the merozoite surface and seem to interact with erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant forms of MSP-2 have been reported to form amyloid fibrils in solution 38 and it is believed that native MSP-2 based higher order aggregates like those seen in the amyloid fibrils may be present in the fibrillar surface coat of the merozoites. 38 The unstructured properties of recombinant forms of MSP-2 would need to be strongly considered in pre-clinical vaccine development programs with this antigen. Monomeric recombinant MSP-2 may not represent the dominant conformation adopted by native MSP-2 on the merozoite surface.…”
Section: Lessons Learnt From the Past Future Directions And Challengesmentioning
confidence: 99%